2018
DOI: 10.5506/aphyspolb.49.523
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Low-lying States in $^{133}$Sn Populated in the $\beta $ Decay of $^{133}$In Using Isomer-selective Laser Ionization

Abstract: Excited states in the neutron-rich isotope 133 Sn were studied via the β decay of 133 In. Isomer selective ionization using the ISOLDE RILIS enabled the β decays of 133 In gs (I π = 9/2 +) and 133m In (I π = 1/2 −) to be

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The analysis of the β-γ -γ data confirmed that the 854-keV and 513-keV transitions are in coincidence with each other and therefore follow the decay of the I π = (1/2 − ) isomer [18]. The observed (1/2 − ) → 3/2 − → 7/2 − cascade supports the low-spin assignment for the decaying state in the progenitor (see (Fig.…”
Section: B β Decay Of the Isomeric State Of 133m In I π = (1/2 − )supporting
confidence: 66%
See 2 more Smart Citations
“…The analysis of the β-γ -γ data confirmed that the 854-keV and 513-keV transitions are in coincidence with each other and therefore follow the decay of the I π = (1/2 − ) isomer [18]. The observed (1/2 − ) → 3/2 − → 7/2 − cascade supports the low-spin assignment for the decaying state in the progenitor (see (Fig.…”
Section: B β Decay Of the Isomeric State Of 133m In I π = (1/2 − )supporting
confidence: 66%
“…The quality of isomer selective laser ionization achieved in our experiment was demonstrated in Ref. [18], where we discussed the population of previously reported low-lying states in 133 Sn. An indication of the presence of the (1/2 − ) isomeric state of 133 In in the implanted beam is the detection of the 854 keV γ ray emitted from (3/2 − ) state in 133 Sn, whereas the line at 1561 keV, corresponding to depopulation of the (9/2 − ) state in 133 Sn, is the signature of the (9/2 + ) ground-state content.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…More details on the isomer selection can be found in Ref. [26]. Following the ionization, indium ions were extracted and accelerated by a 40-kV potential difference, mass analyzed [27], and implanted on an aluminized mylar tape located at the center of our detector setup at the ISOLDE Decay Station (IDS) [28].…”
Section: Methodsmentioning
confidence: 99%
“…Neutron-rich indium isotopes around the doubly magic 132 Sn nucleus are a center of attention and they are extensively studied via a plethora of experimental methods, such as mass measurements [1][2][3][4], laser spectroscopy [5,6], decay spectroscopy [7][8][9][10][11][12][13][14][15][16][17][18], and transfer reactions [19]. It is because nuclei around the doubly magic core are relatively simple systems and they constitute a perfect testing ground for various theoretical approaches [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%